Stent-Assisted Coiling of Ruptured and Incidental Aneurysms of the Intracranial Circulation Using Moderately Flow-Redirecting, Braided Leo Stents—Initial Experience in 39 Patients - Voigt, Peter; Schob, Stefan; Jantschke, Robert; Nestler, Ulf; Krause, Matthias; Weise, David; Lobsien, Donald; Hoffmann, Karl-Titus; Quäschling, Ulf (Frontiers in Neurology, 2017)
Background: Flow diversion – a young technique using stents with highly increased surface coverage – was introduced to treat complex aneurysms without intra-aneurysmal material placement and has amended the spectrum of endovascular techniques like stent assisted coil occlusion considerably. However, ischemic complications, a common side-effect in flow diversion, occur more frequently compared to the conventional endovascular approaches and certainly limit the indication of this technique. Our study aimed to investigate the feasibility and efficacy of stent-assisted coiling using LEO stents, which exhibit only moderate flow redirecting properties and therefore represent a combination of hemodynamic endovascular and occlusive endo-saccular therapy. Material and Methods: 39 Patients were included in our retrospective study. Occlusion rates were assessed 6 months after the procedure in a total of 27 cases using the Raymond scale. Results: Complete occlusion (Raymond I) was achieved in 24/27 aneurysms. Small neck remnants (Raymond II) were evident in 3/27 aneurysms. There were no cases with sac remnant or complete persistence of aneurysmal filling (Raymond III and IV). Conclusion: Our study demonstrates interventional treatment of intracranial aneurysms using flow redirecting stent assisted coiling to be technically feasible and highly effective in aneurysmal occlusion. We believe that this approach is outstanding in the prevention of long-term aneurysmal reperfusion and exhibits a more acceptable risk profile than highly efficient flow diversion techniques.